Analisa Umur Kerja Generator: Analysis Lifetime of Generator Based On It’s Calculate Insulation - Wawoh, Devi; Mangindaan, Glanny; Patras, Lily (Jurnal Teknik Elektro dan Komputer, 2024)
Abstract — Synchronous generators are one of the components that play an important role in power generation. If there is a failure in the generator, the operation stops and will result in the cessation of business and considerable losses. The main cause of failure in generators lies in the stator winding, especially in its insulation condition. Based on the factors that cause the quality of generator insulation to decrease, it will automatically affect the workability or life of the generator. The purpose of this study is to evaluate the performance of the generator during its working life and to analyze the condition of the generator based on insulation resistance testing and delta tangent testing. From the tests that have been carried out, the results of the insulation resistance test are obtained with a resistance value of more than 1 MΩ. So it can be stated that the insulation condition is still good because it has a resistance value of more than 1 MΩ. As for the tan delta test carried out on each phase (U,V,W) from the tests results it can be concluded that the condition is in good condition because the smaller the tangent delta value, the better the generator insulation condition. Keywords — Delta Tangent; Generator; ; Insulation Resistance; Lifetime   Abstrak — Generator sinkron merupakan salah satu komponen yang berperan penting dalam pembangkitan tenaga listrik. Jika terjadi kegagalan pada generator, operasi terhenti dan akan mengakibatkan terhentinya bisnis dan kerugian yang cukup besar. Penyebab utama kegagalan pada generator terletak pada belitan stator, terutama pada kondisi isolasinya. Berdasarkan faktor yang menyebabkan kualitas isolasi generator menurun, maka secara otomatis akan mempengaruhi kemampuan kerja atau umur pada generator. Tujuan dari penelitian ini yaitu untuk mengevaluasi kinerja generator selama umur kerjanya serta untuk menganalisa kondisi generator berdasarkan pengujian tahanan isolasi dan pengujian tangen delta. Dari pengujian yang telah dilakukan di PLTP Lahendong, didapatkan hasil pengujian tahanan isolasi dengan nilai tahanan lebih dari 1 MΩ. Sehingga dapat dinyatakan kondisi isolasinya masih baik karena memiliki nilai tahanan lebih dari 1 MΩ. Adapun pengujian tan delta yang dilakukan pada masing-masing phase (U, V, W) dari hasil pengujian bisa disimpulkan keadaannya dalam kondisi baik karena semakin kecil nilai tangen delta maka semakin baik kondisi isolasi generatornya, Kata kunci — Generator; Umur Kerja; Tahanan Isolasi; Tangen Delta